2022
DOI: 10.1186/s13018-022-02959-z
|View full text |Cite
|
Sign up to set email alerts
|

Heterotopic ossification after total hip arthroplasty: When is development completed?

Abstract: Background Heterotopic ossifications (HO) are a common complication after total hip arthroplasty (THA). Nonsteroidal anti-inflammatory drugs have proven to reduce the occurrence of HO. It is still unclear when the formation of HO is finished. Aim of our study was to answer this question. Methods In a prospective study, the occurrence of periarticular HO was checked during the follow-up (FU) examinations. In total, 75 consecutive patients who underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…Thirdly, we did not evaluate the effect of ASA on patients undergoing THA with different risk profiles for HO due to limited information. A fourth limitation was the inconsistent follow‐up period across included papers; more importantly, they are relatively short to capture HO, based on a recent study suggesting that the formation of HO is complete in 3 years after THA 48 . Notwithstanding these limitations, the present study addresses the shortcoming of prior studies and assists in our understanding of the role of ASA played in the management of THA, providing an abundant room for further research progress in the future.…”
Section: Discussionmentioning
confidence: 96%
“…Thirdly, we did not evaluate the effect of ASA on patients undergoing THA with different risk profiles for HO due to limited information. A fourth limitation was the inconsistent follow‐up period across included papers; more importantly, they are relatively short to capture HO, based on a recent study suggesting that the formation of HO is complete in 3 years after THA 48 . Notwithstanding these limitations, the present study addresses the shortcoming of prior studies and assists in our understanding of the role of ASA played in the management of THA, providing an abundant room for further research progress in the future.…”
Section: Discussionmentioning
confidence: 96%
“…One prospective study of 75 patients given routine etoricoxib after noncemented THA reported that the formation of HO was not completed until 3 years. 31 However, compliance with medication was poor, and only nine patients increased one Brooker stage between 1-year and 3-year follow-up time. 31 The maturation of HO can be evaluated on plain radiographs or CT scans, but sometimes the HO can only be seen on lateral radiographs.…”
Section: Clinical and Radiographic Evaluationmentioning
confidence: 92%
“…31 However, compliance with medication was poor, and only nine patients increased one Brooker stage between 1-year and 3-year follow-up time. 31 The maturation of HO can be evaluated on plain radiographs or CT scans, but sometimes the HO can only be seen on lateral radiographs. 2 A normal serum alkaline phosphatase level may suggest maturation of the bone.…”
Section: Clinical and Radiographic Evaluationmentioning
confidence: 92%
See 2 more Smart Citations